The potency of yellow pigment extract from the marine bacterium Pseudomonas oryzihabitans SAB E-3 as an antioxidant agent - DELFIANI ANGGIAS PUTRI; RIKA INDRI ASTUTI; ARIS TRI WAHYUDI (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Putri DA, Astuti RI, Wahyudi AT. 2024. The potency of yellow pigment extract from the marine bacterium Pseudomonas oryzihabitans SAB E-3 as an antioxidant agent. Biodiversitas 25: 2565-2575. Metabolic processes in cells can produce byproducts in the form of Reactive Oxygen Species (ROS). Excessive amounts of ROS are one of the causes of oxidative stress. Antioxidants are known to act as free radical-scavenging compounds. Pigment-producing bacteria associated with sponges have been widely reported to have antioxidant compounds. In this study, the marine bacterium Pseudomonas oryzihabitans SAB E-3 produced intracellular yellow pigments with potential antioxidant activity. Therefore, this study aimed to assess the in vitro antioxidant and mitochondrial activity at the cellular level and identify chemical compounds. The intracellular pigments produced by P. oryzihabitans SAB E-3 were extracted using methanol, acetone, chloroform, and ethyl acetate. The methanol pigment extract contained the highest number of phenolic and flavonoid compounds, which may have contributed to its antioxidant activity. Furthermore, the active fraction obtained from the bioautographic TLC and harvested using preparative TLC had stronger antioxidant activity against DPPH radicals (75.71 µg/mL) than the crude pigment extract. However, the ABTS radical-reducing activity was lower (226.59 µg/mL) than the crude pigment extract. The maximum wavelength of the pigment extract was 453 nm, indicating the presence of carotenoids. In addition, the lowest concentration of the crude pigment extract (50 µg/mL) and selected active fractions (18.75 µg/mL) increased yeast Schizosaccharomyces pombe ARC039 tolerance to oxidative stress and induced mitochondrial activity. Active fraction one extract analyzed using LC-MS/MS contained piceatannol, resveratrol, isorhapontigenin, isoliquiritigenin, liquiritin, and 2-Omethylisohemigossylic acid lactone, which may contribute to its antioxidant activity. Therefore, the yellow pigment extract and the active fraction produced by P. oryzihabitans SAB E-3 are potential candidates for natural antioxidant sources.